ANALISIS STRUKTUR DAN NILAI-NILAI ESTETIKA DALAM NOVEL INDONESIA (International Forum of Researchers and Lecturers, 2023)
This article aims to describe the aesthetic values found in novels. Aesthetic values in novels are a form of creativity of the author. Aesthetic values include beauty in terms of language, storytelling, depiction of nature that is so real, character features, and depiction of the environment. The beauty of the character description of each character that is packaged in the unity of the sentence is the background of research related to the aesthetics contained in Indonesian novels. The data collection of this research is done by reading and writing techniques using the library research method and is descriptive in nature with data sources coming from Indonesian novels. The author describes the aesthetic value based on the beauty of the language chosen appropriately. The aesthetic values in the novel can be seen from the strengthening of the character, the use of figurative words and the hyperbolic depiction of the storyline. The results of this study can be an insight for literature lovers and focus on sentences that arouse readers' emotions